The psychological impact of COVID-19 on health care workers working in a unique environment under the umbrella of Qatar Red Crescent Society - Muna Abed Alah (14779534) (2021)
Objectives to determine the levels of depression, anxiety, and stress among healthcare workers (HCWs) working in a unique male-dominated environment under the umbrella of Qatar Red Crescent, and to explore the associated factors during COVID-19 pandemic in Qatar. Methods a cross-sectional study utilizing a web-based survey was conducted in the period between 15 November 2020 and 22 December 2020. Depression, anxiety, and stress were determined using the 9-items patient health questionnaire (PHQ-9), the 7-item generalized anxiety disorder (GAD-7) scale, and the 22- item impact of event scale revised (IES-R), respectively. We conducted multivariable logistic regression analysis to determine the predictors of mental health outcomes among HCWs. Results the proportions of the participants reporting symptoms of depression, anxiety, and stress were 12.4 (95%CI: 9.3–16.1), 14.2 (95%CI: 10.9–18.1), and 18.5% (95%CI: 14.8–22.7) respectively. Arabs had significantly more severe anxiety levels than non-Arabs (p = 0.031), HCWs with high COVID-19 risk perception experienced more severe mental health outcomes (p < 0.001). The multivariable logistic regression showed that high risk perception was independently associated with depression (adjusted OR 4.62, 95%CI: 2.00–10.68), anxiety (adjusted OR 4.90, 95%CI: 2.24–10.68), and stress (adjusted OR 3.067, 95%CI: 1.62–5.79) with p < 0.001. Compared to nurses, technicians and paramedics were more likely to report anxiety symptoms with (adjusted OR 2.97, 95%CI: 1.23–7.17, p = 0.015), and (adjusted OR 5.48, 95%CI: 1.86–16.12, p = 0.002) respectively. Having a relative or a friend died of COVID-19 infection was significantly associated with depression symptoms (adjusted OR 2.54, 95%CI: 1.21–5.36, p = 0.014). Not living with family was significantly associated with the presence of different mental health outcomes. Conclusion relatively lower rates of mental health outcomes in this study compared to others could have several explanations related to the unique characteristics of our target population and their working environment. Ensuring proper mental health support for HCWs is highly recommended. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2021.e07236